A fuzzy based risk assessment model with a real case study - (:unkn) unknown (Springer Verlag, 2020)
Occupational Health and Safety (OHS) is the definition given to the works aimed at eliminating any long- and short-term health problems that may occur due to the work is done. The risk assessment in OHS is defined as work carried out with the aim of determining the hazards that may exist in the workplace and the measures to be taken. Several quantitative and qualitative risk assessment tools exist in the literature to analyze the characteristics of different sectors’ causes of accidents and workplace conditions. The fuzzy sets have been used for more effective rating in risk assessment. In this paper, Interval Valued Pythagorean Fuzzy Analytical Hierarchy Process (IV-PFAHP) method and Interval Valued Pythagorean Fuzzy TOPSIS (IV-PFTOPSIS) method have been suggested to deal with the risk assessment process with a real case study. The paper focuses on IV-PFAHP and IV-PFTOPSIS methods to handle uncertainty in the risk assessment process for health sector. The results revealed that the proposed approach produces reliable outcomes representing the vagueness of the decision-making process. © 2020, Springer Nature Switzerland AG.
Keywords: Fuzzy sets; Occupational health and safety; Risk assessment